Harmonizacja prawa w Unii Europejskiej w dziedzinie usług finansowych - Borowiec, Jan (The European Union Law Harmonization in the Field of Financial Services, 2007)
The realization of freedom to provide financial services is not possible without removing barriers, which rise from legislation of member states. The reason is that financial market belongs to those highly hedged around with the legal regulations. Specific legal rules vary among countries very often and therefore they hamper the access to national financial market for the foreign investors. The treaty establishing the European Community stipulates that the law of member states will converge in a sufficient degree for the common market to function. The aim of the article is to present the legal basis of the law harmonization within the EU and its effects on banking law, insurance sector and capital market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (15); 2007; nr 1166, s. 95-105